On-top Plasty for Reconstruction of Thumb Using Index Finger - Nakarmi, Kiran K. (Journal of Nepal Health Research Council, 2019)
Thumb is very important for hand function. Many options are available to reconstruct injured thumb from simple dressing (pulp injury without bone exposure) to replantation and toe transfer (significant loss of thumb length). In chronic setting, where other fingers are intact, on-top plasty can be used to reconstruct injured thumb. In this study, a case of a boy who lost his thumb in a road accident is presented. Thumb reconstruction was performed using partially injured ipsilateral index finger. At two months, successful restoration of form and function were noted. Keywords: Index finger on-top plasty; thumb injury; thumb reconstruction.